2017
DOI: 10.1021/acscatal.7b02409
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Olefin Metathesis with CAAC-Containing Ruthenium Benzylidenes

Abstract: Several olefin metathesis reactions are studied, namely, jojoba oil oligomerization, methyl oleate self-metathesis, ring-closing metathesis (RCM) to form a nitrogen heterocycle, and 1,5-hexadiene acyclic diene metathesis polymerization (ADMET). The catalyst containing the Bertrand−Grubbs cyclic alkyl amino carbene (CAAC) ligand showed high selectivity by diminishing isomerization reactions; this was especially clear at high temperatures where the more widely used nitrogen heterocyclic carbene (NHC)-based catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 66 publications
5
37
0
Order By: Relevance
“…Olefin metathesis is one of the fundamental catalytic reactions that initiated new industrial technology avenues . The most frequently used olefin metathesis catalysts utilize Re, W, Mo and Ru compounds with the latter being the most preferable metal in homogeneous systems showing exceptional activity in chlorinated solvents and toluene (Scheme ) . Ample effort has already been made to extend the Ru‐based catalyst for applications in environmentally benign, protic or aprotic solvents by introducing appropriate phase tags to the parent complexes .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Olefin metathesis is one of the fundamental catalytic reactions that initiated new industrial technology avenues . The most frequently used olefin metathesis catalysts utilize Re, W, Mo and Ru compounds with the latter being the most preferable metal in homogeneous systems showing exceptional activity in chlorinated solvents and toluene (Scheme ) . Ample effort has already been made to extend the Ru‐based catalyst for applications in environmentally benign, protic or aprotic solvents by introducing appropriate phase tags to the parent complexes .…”
Section: Methodsmentioning
confidence: 99%
“…[2,3] The most frequently used olefin metathesis catalysts utilize Re, W, Mo and Ru compounds with the latter being the most preferable metal in homogeneous systems [4] showing exceptional activity in chlorinated solvents and toluene (Scheme 1). [5][6][7][8][9] Ample effort has already been made to extend the Ru-based catalyst for applications in environmentally benign, protic [10,11] or aprotic solvents [12,13] by introducing appropriate phase tags to the parent complexes. [14] Yet, the presently known arsenal of such Ru olefin metathesis catalysts, including numerous quaternary amino derivatives, [10][11][14][15][16][17][18][19][20] is far from industrial practicability as too high, 2-5 mol % catalyst loadings are required to achieve reasonable substrate conversions.…”
Section: Towards Sustainable Catalysis -Highly Efficient Olefin Metatmentioning
confidence: 99%
“…[12a,73] Even though the involvement of these ruthenium-hydride species is not certain, [74] olefin migration was avoided or limited by the presence of additives such as 1,4benzoquinone, the use of first generation ruthenium catalysts and more recently by the design of catalysts with no isomerizing properties. [75] It is also noteworthy that as observed in many metathesis transformations, the catalysts and substrates impurities can be source of isomerization reactions. [73b] On the other hand, advantage could be taken from this facile double bond migration to further generate functional styrene derivatives upon subsequent cross metathesis (Scheme 28).…”
Section: Isomerization and Cross Metathesismentioning
confidence: 99%
“…The synthetic limitations of previously reported catalysts motivated the design of a catalyst able to survive in bulk above the polymer T m while minimizing olefin isomerization . Grubbs and Bertrand prepared and investigated ruthenium catalysts containing cyclic (alkyl)(amino) carbene (CAAC) ligands (Figure , structure “d”) .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to their NHC predecessors, CAAC‐substituted catalysts are more selective for metathesis over olefin isomerization; further, they yield significantly higher turnover numbers in cross metathesis, ring‐closing metathesis, and ethenolysis, including formation of terminal olefins . Prior to the research reported here, catalysts containing CAAC ligands have been utilized for cross metathesis, ring‐closing metathesis, ring‐opening metathesis polymerization, and non‐bulk ADMET conversions …”
Section: Introductionmentioning
confidence: 99%